The Influence of Education and Training and Competency Through the Curriculum on Performance Improvement - Hatina, Damaida; Mellita, Dina (Journal of Social Work and Science Education, 2023)
The purpose of this study was to determine and analyze the effect of education and training on increasing performance, the effect of competence on increasing performance, the effect of curriculum on increasing performance, the effect of education and training on competence, the effect of curriculum on moderating education and training on increasing performance and the influence of curriculum on moderating competency on improving the performance of auxiliary Syahbandar. In this study using primary data and secondary data, primary data was obtained through distributing questionnaires with a sample of 210 people who were alumni of the Training of Fundamentals of Armed Forces of the Palembang River Lake and Ferry Transportation Polytechnic. The data analysis technique used is Partial Least Square Structural Equation Modeling (PLS SEM) using the SMARTPLS application. From the results of data analysis, it was found that education and training variables and curriculum variables did not have a significant direct effect on performance, competency variables directly had a significant effect on performance, education and training variables had a significant effect on competence, and curriculum variables did not strengthen in moderating the influence of education and training variables. training on performance improvement as well as curriculum variables did not strengthen in moderating the effect of competency variables on improving the performance of the auxiliary Syahbandar.